FROM BLENDED LEARNING TO ONLINE LEARNING: A JAVA PROGRAMMING COURSE CASE STUDY - Amelia Jati, Robert Jupit; Ping Ping, Tan (UMK Press, 2021)
Before the innovation was introduced, interactions occur more frequently in classroom instead of online in blended learning. The online component of blended learning tends to focus more on passive activities such as downloading online lecture notes or as a tool to select members for group projects. Even with full online learning, recorded lecture videos are still passive learning for the students. Without face-to-face interaction, how far do the students understand after watching the videos remain unknown and to wait till after the students have taken the test, it will be too late to help the students. Furthermore, one-way learning can be boring and students might lose interest after watching one or two videos, which we do not want in full online learning. In addition, not all online learning activities are suitable to assist students to learn programming.